Multiscale damage plasticity modeling and inverse characterization for particulate composites. (October 2020) - Lim, Hyoung Jun; Choi, Hoil; Zhu, Fei-Yan; Kerekes, Tomas Webbe; Yun, Gun Jin
Abstract: In this paper, we propose a multiscale damage plasticity model for particulate composites within an incremental Mori-Tanaka (MT) micromechanics framework and present numerical and experimental verification. J 2 plasticity and Lemaitre-Chaboche ductile damage models account for damage in the matrix and a linear spring model accounts for interface damage between the matrix and inclusions. Local and global strain concentration tensors are iteratively updated by minimizing errors caused by the constantly changing algorithmic tangent operator of the ductile damage matrix. Finite element (FE)-based direct numerical simulation (DNS) models are used as baseline models for verification. Properties of the ductile damage matrix and interface damage variables are inversely identified from experimental data. FE-MT multiscale damage plasticity model with the identified properties are experimentally verified with uniaxial tensile test results of glass bead/epoxy composites. Ductile damage evolution and patterns from the proposed model are verified with digital image correlation (DIC) test results. Increasing porosity within the matrix and interface damage from micro-computed tomography (CT) and microscope, respectively, prove the importance of damage modeling in the prediction of structural response by the model. Highlights: A multiscale damage plasticity model for particulate composites is integrated within Mori-Tanaka micromechanics framework. Properties of the ductile damage matrix and interface damage variables are inversely identified from experimental data. The FE-MT multiscale damage plasticity model with the identified properties are experimentally verified. Experimental evidence of the damage proves the importance of damage modeling in the prediction of behavior of materials.